Born Toon Soon: Preterm birth matters - Howson, Christopher P; Kinney, Mary V; McDougall, Lori; Lawn, Joy E (Reproductive health, 2013)
Doc number: S1 Abstract: Urgent action is needed to address preterm birth given that the first country-level estimates show that globally 15 million babies are born too soon and rates are increasing in most countries with reliable time trend data. As the first in a supplement entitled "Born Too Soon", this paper focuses on the global policy context. Preterm birth is critical for progress on Millennium Development Goal 4 (MDG) for child survival by 2015 and beyond, and gives added value to maternal health (MDG 5) investments also linking to non-communicable diseases. For preterm babies who survive, the additional burden of prematurity-related disability may affect families and health systems. Prematurity is an explicit priority in many high-income settings; however, more attention is needed especially in low- and middle-income countries where the invisibility of preterm birth as well as its myths and misconceptions have slowed action on prevention and care. Recent global attention to preterm birth hit a tipping point in 2012, with the May 2 publication of Born Too Soon: The Global Action Report on Preterm Birth and with the 2nd annual World Prematurity Day on November 17 which mobilised the actions of partners in many countries to address preterm birth and newborn health. Interventions to strengthen preterm birth prevention and care span the continuum of care for reproductive, maternal, newborn and child health. Both prevention of preterm birth and implementation of care of premature babies require more research, as well as more policy attention and programmatic investment. Declaration: This article is part of a supplement jointly funded by Save the Children's Saving Newborn Lives programme through a grant from The Bill & Melinda Gates Foundation and March of Dimes Foundation and published in collaboration with the World Health Organization (WHO). The original article was published in PDF format in the WHO Report "Born Too Soon: the global action report on preterm birth (ISBN 978 92 4 150343 30). The article has been reformatted for journal publication and has undergone peer review according to Reproductive Health 's standard process for supplements and may feature some variations in content when compared to the original report. This co-publication makes the article available to the community in a full-text format.